Expenditures on Hotel and Catering Services in Polish Households and its Determinants - Wołoszyn , Andrzej; Ratajczak , Karolina; Stanisławska, Joanna (Studia Oeconomica Posnaniensia, 2018)
The study aimed to assess the incidence and the level of expenditures on hotel and catering services in Polish household budgets between 2005 and 2015, and to identify determinants of the demand for these services. The source data came from the individual micro data of the HBS conducted by the Central Statistical Office in 2005, 2010, and 2015. Initially in 2005, relatively few households reported any expenditure on hotel and catering services, namely 3% and 14%, respectively. Over the studied period, both the incidence and the level of the expenditures were observed as rising steadily, but by no means evenly. The incidence of catering services expenditure and its growth was found higher than that of hotel services, while the level of the expenditures and its growth was lower. Among determinants that discriminate the effective demand for hotel and catering services most prominent turned out to be, beside income, preference-shaping social factors, such as education and the age of the household head or household residence area.